The Learning Styles and Approaches of Students Studying the Fundamental Algorithmic Concepts course at the University of the Witwatersrand - Wedderburn, Linda Anne (My University, 2006)
Many students fail the Fundamental Algorithmic Concepts course, in first year Computer Science at the University of the Witwatersrand. To obtain an understanding of why this occurs, the learning styles and learning approaches of the students studying the course and the relationship of these concepts with student grades were researched. A predominately qualitative paradigm was used, supplemented with quantitative data. Two research designs were selected: a survey to get a broad overview of the sample and an ethnographic design to provide an in-depth description of a small group. Existing instruments were used for the survey, namely Felder and Soloman’s Index of Learning Styles and a learning approach diagnostic test that was constructed in South Africa. An interview with open-ended questions was used for the ethnographic research. Contrary to expectations, the results of the study indicated that the adoption of a deep learning approach did not imply success. The findings suggest that a strategic learning approach may be required to achieve good grades. In contrast to other studies, over 65% of the sample population were black students. It was found that black students tend to adopt a deeper learning approach than the rest of the students. From a learning style perspective there was some new evidence to indicate that the more intuitive or global a student was, the deeper the approach the student adopted to learning. A large percentage (over 80%) of the population were visual learners and an unusually high percentage (over 60%) were reflective learners. The lecturer should match the workload and assessment methods with the desired learning approach of the students. The lecturer should also encourage the students to adopt a strategic learning approach where appropriate. In addition, the lecturer should pay particular attention to incorporating teaching styles that accommodate students with visual and active learning style preferences.
Student Number : 8109673 - MSc research report - School of Science Education - Faculty of Science
Keywords: learning styles; science education; learning approaches; computer science education; Fundamental Algorithmic Concepts Course